LOU/c/jall rat as a model of resilience in the context of streptozotocin-induced cognitive impairment - Gephine, Lucas; Corvaisier, Sophie; Bernay, Benoît; Freret, Thomas; Leger, Marianne (Frontiers in Aging Neuroscience, 2025)
IntroductionThe concept of cognitive resilience (CR) has emerged to explain the lack of correlation between the extent of brain lesions and the severity of cognitive symptoms in Alzheimer’s disease (AD), but the underlying mechanisms remain poorly understood.MethodsTo investigate this, we developed a preclinical model of CR using a sporadic model of AD in a specific rat strain named LOU/c/jall described as a successful aging model. LOU/c/jall and Wistar control rats were bilaterally injected with streptozotocin (STZ; 3 mg/kg) or a vehicle solution into the cerebral ventricles. Cognitive performance and neuropathological examinations were evaluated 1 month after surgery.ResultsOur results showed that STZ-injected Wistar exhibited greater cognitive deficits than LOU/c/jall, despite similar brain alterations, revealing for the first time CR in the LOU/c/jall strain. Proteomic analysis identified differentially expressed proteins involved in the AD pathway between the two strains.DiscussionUnderstanding the role of these proteins in AD could improve our understanding of the brain mechanisms underlying CR and guide the development of more targeted therapeutic strategies.